Solving Airport Gate Allocation Problem using Simulated Kalman Filter - Zulkifli, Md. Yusof; Siti Nurzulaikha, Satiman; Kamil Zakwan, Mohd Azmi; Badaruddin, Muhammad; Saifudin, Razali; Zuwairie, Ibrahim; Zulfakar, Aspar; Suraya, Ismail (Universiti Sains Malaysia, 2016)
Airport gate allocation problem refers to the search for optimal assignment of flights to gates at an airport. Assignment of flight to gates has become very complex nowadays, especially for a big size airport. In this study,the airport gate allocation problem is solved using a recently introduced meta-heuristic called simulated Kalman filter (SKF). The SKF is driven by the estimation capability of a well-known Kalman filter. The objective of this study is to minimize the total walking distance. Since the airport gate allocation problem is a combinatorial optimization problem, the original SKF is extended such that it can be used to solve combinatorial optimization problems. A small case study with 15 flights and 16 gates has been chosen. Preliminary results show that SKF is a promising algorithm for solving the airport gate allocation problem.